Long-term survival after surgical intervention for bone disease in multiple myeloma - Zeifang, Felix; Zahlten-Hinguranage, Anita; Goldschmidt, Hartmut; Cremer, Friedrich Walter; Bernd, Ludger; Sabo, Desiderius (Annals of oncology, 2005)
Background - We describe the surgical treatment, outcome and long-term survival of patients with multiple myeloma (MM) in response to conventional (CC) or high-dose (HDT) chemotherapy. - Patients and methods - Eighty-four patients diagnosed with MM were recruited for the study (51 male, 33 female; median age 62 years) and consecutively surgically treated in a single institution during a 12-year period. The main end point of the study was overall survival after surgery. Cox regression analysis was used to estimate the effect of factors that may predict survival. - Results - Spinal surgery was performed in 54 cases, and 30 patients were surgically treated at the extremities. The post-surgical complication rate was low (17%; 14/84 patients). The median overall survival time was 47 months. Patients receiving HDT had a longer 5-year overall survival rate than patients receiving CC (51% versus 33%). Univariate predictors of mortality included age >65 years [risk ratio (RR) 1.62; P=0.023], osteolyses in long weight-bearing bones (RR 2.23; P=0.007) and an elevated C-reactive protein level >5mg/l (RR 1.82; P=0.016); the latter remained significant as a predictor in multivariate analysis (RR 2.66; P=0.0209). - Conclusions - Given the high number of patients reaching 5-year overall survival and the low post-surgery complication rate, surgery should pursue a long-term stable reconstruction of the affected bone.